a Overview of Adolescent Mental Health in Boarding Schools - Noveri Aisyaroh; Suryo Ediyono (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Human life is not free from stress in their daily lives, including adolescents. Adolescents tend to be more sensitive to their surroundings which can affect emotions. Mental health disorders have started to occur since adolescence (15-24 years) with a prevalence of 6.2%. The impact of mental health disorders in adolescents can reduce learning achievement. The purpose of this study was to determine the description of adolescent mental health in boarding schools. The type of research is descriptive quantitative with a cross sectional approach, respondents were MA students in class XII who were in boarding schools totaling 40 students. Data were collected using the Strengths & Difficulties Questionnaire (SDQ) and analyzed univariately. The results showed that most of the respondents were male (67.5), parental education (father by 42.5% and mother by 47.5%), father's work as a private employee (32.5%), mother's work as a housewife (35%). The mental health picture of respondents on the difficulty score is mostly in the threshold / moderateline condition (40%) and the strength score is mostly in normal condition (95%). The need for early detection of mental health in adolescents in schools using the Strengths & Difficulties Questionnaire (SDQ).